Aspern Explained: How the Discursive Institutionalisation of Infrastructure Planning Shaped North-Eastern Vienna's Urban Transformation. Issue 2 (2nd April 2020) - Krisch, Astrid; Suitner, Johannes
Abstract: This paper investigates planning and development processes of networked infrastructure systems from an institutional perspective. It applies theories of ASID (agency, structure, institutions, and discourse) and discursive institutionalism to unveil simplistic structure-agency imaginaries of infrastructure planning. The concept of discursive institutionalism puts emphasis on ideas that are discursively constructed by agents, forming the basis for collective action. This allows understanding of (1) the idealised structure of society, (2) the envisioned future city, and (3) the disciplinary self-conception of "good planning" as key intermediary instances of development and change. Through the case study of the Aspern area in north-eastern Vienna, the paper explores the origins of material urban transformations from cropland to strategic development site by focusing on the discursive institutionalisations of infrastructure planning since 1954. It points to institutionally stable phases of infrastructure planning as well as critical transitions in the planning system – all shaping Aspern's subsequent development. Retracing this process through content analysis, interviews and archival research serves as an explanation to the multi-layered interdependencies of the entailing realisation of a small-scale urban development project. Herewith, the research contributes to a better understanding of the impact of planning discourse on urban development and the discursive institutionalisation of infrastructure planning.